An Experimental and Simulated Study on Gas-Liquid Flow and Mixing Behavior in an ISASMELT Furnace - Hongliang Zhao; Tingting Lu; Pan Yin; Liangzhao Mu; Fengqin Liu (Metals, 2019)
In this study, a water-model experiment and numerical simulation were carried out in a pilot ISASMELT furnace to study the factors affecting mixing time. The experimental results were compared to the simulation results to test the accuracy of the latter. To study the internal factors that affect the mixing time, the turbulent viscosity and flow field were calculated using simulation. In addition, following previous research, external factors that influence the mixing time including the depth of the submerged lance, lance diameter, gas flow rate, and the presence of a swirler were studied to investigate their effect on the flow regime. The results indicated that the mixing time is controlled by the turbulent viscosity and velocity vector. In addition, it was found that the lance diameter should not exceed 3.55 cm to maintain sufficient energy for stirring the bath. Finally, the optimal gas flow rate that offers the best mixing efficiency was found to be 50 Nm3/h.